Curso de vida e função cognitiva na vida adulta: estudo longitudinal de saúde do adulto (ELSA-BRASIL), 2008-2010 - Larissa Fortunato Araujo (2015)
Introduction: Recently, evidence suggests that cognitive decline in aging is the result of a pathological process that begins around 45 years of age. By the aging of Brazilian population, the burden of neurological disease has influence on public health because it is related to high dependency and mortality in this population. The study of how socioeconomics, nutritional exposures and the cardiovascular risk disease in later life influences on cognitive performance in adults is relevant. The knowledge of risk factors of life course on cognition allows guiding for which stage of life preventive measures will prolong the onset of cognitive decline with aging. It is also relevant the study of food that have a larger consumption from the population, such as coffee, which has bioactive components that can also contribute to preventing cognitive decline. Objectives: The objectives of this thesis are threefold: 1) to estimate the independent effect of low maternal educational attainment, low birth weight and smaller leg and trunk lengths in poor performance on cognitive function tests in adults; 2) analyze the cumulative effect of low maternal educational attainment and nutritional markers of malnutrition in poor performance on cognitive function tests in adults; 3) explore the independent effect of low maternal educational attainment, smaller trunk length and the higher cardiovascular risk disease in 10 years by the Framingham Risk Score on poor global cognition in adults; 4) to investigate the cumulative effects of worse socioeconomic and nutritional conditions throughout life, and the higher risk for cardiovascular disease in 10 years by the Framingham Risk Score are associated with poor global cognition and different domains of cognitive function in adults; and 5) analyze the relationship of coffee consumption in the last 12 months with global cognition and different domains of cognitive function in adults and elderly; and 6) to estimate the amount of coffee consumption per day that would be related to better global cognitive performance and in different domains of cognitive function in adults and elderly. Methodology: The sample of this study is from the baseline of the Brazilian Longitudinal Study of Adult Health, comprised of 15,105 adults and elderly, government employees from universities and research centers located in six Brazilian states: Minas Gerais, São Paulo, Rio de Janeiro, Espírito Santo, Bahia and Rio Grande do Sul. Three papers were developed, in the first article, the response variables were three different tests of cognitive function categorized into a binary variable which the worst decile was compared with the others. By multiple logistic regression in a adulthood population (35-64 years old), we estimated the chance of being in the worst decile of cognitive performance when exposed to the following markers of socioeconomics and nutritional conditions of life course, such as lower maternal education, lower birth weight, and smaller leg and trunk lengths. In the second article by multiple linear regression, we explored whether participants that were exposed to unfavorable socioeconomic (lower maternal education) and nutritional (smaller trunk lengths) conditions throughout life, and higher cardiovascular risk disease measured by Framingham Risk Score is associated with worse performance on global cognition and on three different tests of cognitive function in adulthood (35-64 years old). The third article, we estimated by multiple linear regression and generalized linear model if coffee in categories of consumption was associated with better performance on global cognition and also on various tests of cognitive function in adults and elderly (35-74 years old) Results: In the first article, after mutual adjustments with all variables of exposure, we found that lower maternal educational attainment was associated with a dose-response gradient with higher chance of poor performance on all cognitive function tests. Low birth weight was associated with a higher chance of poor performance in trail-making test version B, also the trunk length in the phonemic verbal fluency tests and trail-making test version B. The leg length was not associated with any cognitive function test. The associations observed were not modified by the current educational level of the participant. The second article, the cumulative effect of lower maternal educational attainment, smaller trunk length and higher cardiovascular risk disease, was associated with worse performance on global cognition and also on learning, recall and word recognition tests, semantic and phonemic verbal fluency tests, and the trail-making test version B in adulthood. The third article, after adjustments for current socioeconomic, demographic and health conditions, higher consumption of coffee cups per day in the last 12 months was associated with better performance in learning, recall and word recognition tests and worse performance trail-making test version B in adults and elderly. Conclusions: The present study found that exposure to unfavorable socioeconomic and nutritional conditions in early life, represented by lower maternal educational attainment, lower birth weight and smaller trunk lengths has an independent and negative effect on semantic memory, learning, attention, executive control and language in a cohort of Brazilian adults. Our results suggest that the current educational attainment mitigates but does not completely remove the association between poor socioeconomics and nutritional conditions during childhood and adolescence and worse cognitive performance, especially in executive control. The results of this study are consistent with published studies demonstrating the importance of socioeconomic and nutritional conditions in early life, as well as the cardiovascular risk diseases estimated by the Framingham Risk Score on cognitive performance in adulthood. An extensive understanding of the social determinants of health and cognitive functioning in aging, requires attention to unfavorable exposures to health throughout life, with particular focus on certain periods (as in childhood, adolescence and early adulthood life), as well as the knowledge of cumulative effect. The coffee consumption until 4 cups per day may have a protective neurodegenerative effect on memory and also prevents the detrimental effect on executive function in adults and elderly, even after adjustment for confounding variables that might be associated with a mechanism of reverse causality. Social, nutrition and materials interventions throughout the life cycle, especially during early life can have a substantial impact in reducing and/or delay in cognitive decline in aging.